Perbandingan Pengaruh Atribut Iklan Viral yang Dipilih Terhadap Belanja Perilaku Generasi Milenial - Studi Empiris - Megra Maulana; Nanang Wahyudin (STIE Amkop Makassar, 2024)
This study aims to evaluate how specific viral advertising elements affect Millennial consumers' purchasing decisions. We completed these two stages to reach our goal: The authors' initial step involved figuring out how the chosen features affected consumers' overall buying habits. Additionally, in the second phase, the effects of two research initiatives will be compared: ABSOLUT's viral campaign and 4KA's guerilla efforts. 360 respondents filled out a questionnaire about a sample of young clients, which provided the data for the analysis. The collaborative and cooperative millennial generation (1975-2000) Technology should only be used for passionate values and adventurous activities. The eight characteristics listed in the survey section of the questionnaire were innovation, relevance, aesthetics, clarity, comedy